THE EVALUATION OF STRAWBERRY PRODUCTION IN ANAMUR PROVINCE AGAINST RURAL POVERTY (Third Sector Social Economic Review, 2019)
Rural poverty in Turkey; Mainly has in agricultural areas. Because the main field of activity of the rural sector is agricultural activities. Anamur District is known as a place where banana growing has been done intensively in Turkey for many years. Strawberry farming has become a source of hope for labor-intensive labor in the rural area, lower capital requirements, lower yielding opportunities for production at Anamur, and poverty and deprivation for low-income, small-scale people. Strawberry production is creating a chance to live in small family businesses instead of a production style that requires high investment such as banana in Anamur. Strawberry production is an important mode of production for low-income, small-scale family businesses from poverty and deprivation.
Keywords: Poverty; Rural Poverty; Strawberry Production; Anamur